2016
DOI: 10.1117/12.2212420
|View full text |Cite
|
Sign up to set email alerts
|

A compact polymer optical fibre ultrasound detector

Abstract: Keywords: Polymer Optical Fibre Sensors, Fibre Sensors, Polymer Optical Fibre, Endoscopy, Biomedical Applications , UltrasoundPolymer optical fibre (POF) is a relatively new and novel technology that presents an innovative approach for ultrasonic endoscopic applications. Currently, piezo electric transducers are the typical detectors of choice, albeit possessing a limited bandwidth due to their resonant nature and a sensitivity that decreases proportionally to their size. Optical fibres provide immunity from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In 2015, Broadway et al showed the POF potential for endoscopic operation [35]. Recently, the same group presented for the firs time opto-acoustic measurements using a microstructured polymer optical fibe (mPOF) FBG with a 130 μm diameter fibe and presented the lateral directivity pattern of an ultrasound sensor over a frequency range of 1-50 MHz [36], [37]. These works showed that the acoustic sensitivity for POF is 13 times higher than for silica optical fibe .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Broadway et al showed the POF potential for endoscopic operation [35]. Recently, the same group presented for the firs time opto-acoustic measurements using a microstructured polymer optical fibe (mPOF) FBG with a 130 μm diameter fibe and presented the lateral directivity pattern of an ultrasound sensor over a frequency range of 1-50 MHz [36], [37]. These works showed that the acoustic sensitivity for POF is 13 times higher than for silica optical fibe .…”
mentioning
confidence: 99%
“…These works showed that the acoustic sensitivity for POF is 13 times higher than for silica optical fibe . Furthermore, 3 times more sensitivity can be achieved using mPOF than with the other POFs and a potential transition from uniform POFBGs to Fabry-Perot cavities or phase-shifted POFBGs (PS-POFBGs) can expand the potential that POF has to offer in this fiel [36], [37]. The goal with that is to deliver a narrower spectral shape, which can potentially be used to achieve higher sensitivities.…”
mentioning
confidence: 99%
“…The growing body of progress on polymer is driven by the fundamental characteristics of said fibre, best expressed through the most characterized variety of PMMA. PMMA typically has an elastic limit of 10% and a Young's Modulus of 3.2GPa [2] with specific positive results with relation to acoustic sensitivity [3]. It is important to stress that all polymer fibres have varying characteristics that include both advantages and disadvantages and that for a given application, it is important to consider the entire range of polymers to identify which presents the best proposal overall.…”
Section: Introductionmentioning
confidence: 99%
“…These range from the fundamentals of temperature [4] and strain [4] to fuel level monitoring [5], dosimetry [6], ultrasound [2] and humidity [7]. To date, both PMMA and TOPAS, a cyclic olefin co-polymer, have been preliminarily examined for ultrasound detection, in interferometric [3] and later fibre Bragg grating (FBG) sensing modalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…The wide variety of sensing configurations, materials, geometry and a typically small size can deliver sensitivity inversely proportional to its own dimensions has led to widespread research into applications from acoustics [9] to humidity [10].…”
Section: Introductionmentioning
confidence: 99%